Single-grain dose-distribution measurements by optically stimulated luminescence using an integrated EMCCD-based system - Greilich, Steffen; Gribenski, Natacha; Mittelstraß, Dirk; Dornich, Kay; Huot, Sebastien; Preusser, Frank (Quaternary geochronology, 2015)
We report on the feasibility of assessing single-grain dose-distributions by using an EMCCD-based imaging system with complementary analysis software. Automated image-processing was successfully applied to compensate sample motion and for grain identification. Following a dose recovery test, 74% of the grains were recognized successfully, and 44% exhibited a suitable OSL dose response behavior to interpolate an equivalent dose value, and a central dose recovery ratio of 1.038 was obtained.
Gesehen am 13.10.2020